Molecular cloning and chromosomal localization of a sarco/endoplasmic reticulum-type Ca[2+]-ATPase of Drosophila melanogaster. - Magyar, A.; Varadi, A. (Biochemical and Biophysical Research Communications, 1990)
We report here the characterization of a Drosophila melanogaster cDNA that encodes a sarco/endoplasmic reticulum-type Ca2(+)-ATPase. Previously we amplified the phosphorylation site - FITC-binding site fragment of this cDNA by Polymerase Chain Reaction utilizing homology primers (Váradi, A., Gilmore-Hebert, M. and Benz, E. J. Jr. (1989) FEBS Letters 258 203-207) and in the present work we used this fragment as probe for isolation of a cDNA clone with the intire coding region. The isolated 3.3 kb clone has been sequenced and the primary structure of the encoded protein has been deduced. It consists of 1002 amino acids with all the characteristic features of the P-type ATPases. It shows 67-71% amino acid identity and an apparently identical hydropathy profile with the mammalian sarco/endoplasmic reticulum-type Ca2(+)-ATPases. On basis of sequence similarity we suggest that the first transmembrane segment of sarco/endoplasmic reticulum type Ca2(+)-ATPases may be responsible for targeting of these transport proteins into the organellar membrane. The gene of this sarco/endoplasmic reticulum-type Ca2(+)-ATPase has been mapped on the right arm of chromosome 2, in section 60A.